2011
DOI: 10.1111/j.1365-2265.2011.04140.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease is associated with higher epicardial Retinol‐binding protein 4 (RBP4) and lower glucose transporter (GLUT) 4 levels in epicardial and subcutaneous adipose tissue

Abstract: Retinol-binding protein 4 levels behave differently in EAT and SAT with respect to CAD. However, both adipose tissues have lower GLUT4 levels in patients with CAD. These findings suggest a differential regulation of RBP4 production in EAT and SAT that may be influenced by local factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 36 publications
3
33
0
2
Order By: Relevance
“…These derangements appear to be related to infiltration of the adipose tissue by macrophages and upregulation of bioactive molecules that could exert their effects through paracrine and vasocrine mechanisms [48,49]. Consistent with this finding, epicardial fat of subjects affected by coronary artery disease was found to be more abundant and to exhibit greater oxidative stress and inflammatory burden than SC fat [50][51][52]. In addition, in obese patients EAT amount was associated with increased left ventricular mass, right ventricular cavity size, atrial enlargement and diastolic dysfunction [53][54][55].…”
Section: Ectopic Fat Depots and Their Local Effectssupporting
confidence: 61%
“…These derangements appear to be related to infiltration of the adipose tissue by macrophages and upregulation of bioactive molecules that could exert their effects through paracrine and vasocrine mechanisms [48,49]. Consistent with this finding, epicardial fat of subjects affected by coronary artery disease was found to be more abundant and to exhibit greater oxidative stress and inflammatory burden than SC fat [50][51][52]. In addition, in obese patients EAT amount was associated with increased left ventricular mass, right ventricular cavity size, atrial enlargement and diastolic dysfunction [53][54][55].…”
Section: Ectopic Fat Depots and Their Local Effectssupporting
confidence: 61%
“…Furthermore, the expression levels of glucose transporter-4 (GLUT4) are lower, whereas those of renitolbinding protein 4 (RBP4) are higher in EAT from CAD compared to non-CAD subjects [46], suggesting that EAT may partly be responsible for local insulin resistance and altered glucose and lipid profile, which, in turn, can promote atherogenic changes in coronary vessels.…”
Section: The Clinical Relevance Of Eat In Coronary Artery Diseasementioning
confidence: 99%
“…Finally, a higher oxidative stress, which also actively participates in the development and progression of atherosclerotic plaques, has been reported in EAT from CAD patients, as shown by higher levels of reactive oxygen species and lower levels of catalase (an antioxidant enzyme) compared to subcutaneous fat [46]. Recent studies have also reported that the increased oxidative stress characterizing EAT of CAD patients is capable of promoting transdifferentiation of brown to white adipocytes [47] and that an increase in 'brown' features of EAT could predict the stability of coronary atheromas in humans [48].…”
Section: The Clinical Relevance Of Eat In Coronary Artery Diseasementioning
confidence: 99%
“…Furthermore, EAT from HF patients expresses lower levels of fatty acid-binding protein 4 (FABP4) (72) and fat-mobilizing genes (35). In addition, loss of diacylglycerol O-acyltransferase 1 (DGAT1) activity in heart muscle reduces gene expression involved in free FA uptake, such as CD36, reducing toxic lipid accumulation in the heart (47).…”
mentioning
confidence: 99%